Evaluasi Model Pengajian-Pengajian Muhammadiyah dan ‘Aisyiyah - Mahmud Yunus Daulay; Nur Rahmah Amini (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This research begins with the needs of Muhammadiyah and 'Aisyiyah cadres in improving the progress of Muhammadiyah's da'wah. Based on the conditions of the problems that occur in Muhammadiyah recitations, it is necessary to have a maximum evaluation to continue to improve Muhammadiyah da'wah, so that the Muhammadiyah organization is more advanced. The research method used is participatory descriptive. Based on the results of interviews and observations made by researchers, it was concluded that it could increase the reactivity of Muhammadiyah and 'Aisyiyah administrators so that recitation activities run optimally. This research activity was carried out by studying Kemuhammadiyahan, explaining the activities of Muhammadiyah branches in each sub-district, evaluating every Muhammadiyah cadre and 'Aisyiyah in recitation activities to improve Muhammadiyah da'wah. Suggestions from the research, it is hoped that all branch and branch managers in each sub-district will continue to be active in recitation, social and community activities.